The dead town [compact disc, unabridged] : a novel - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Dean Koontz's Frankenstein, 2011)
The war against humanity is raging. As the small town of Rainbow Falls, Montana comes under siege, scattered survivors band together to weather the onslaught of creatures set loose upon the world. As they ready for battle against overwhelming odds, they will learn the full scope of Victor Frankenstein's nihilistic plan to remake the future.